Microwave dielectric measurements of erythrocyte suspensions. - Bao, J Z (1994)
Complex dielectric constants of human erythrocyte suspensions over a frequency range from 45 MHz to 26.5 GHz and a temperature range from 5 to 40 degrees C have been determined with the open-ended coaxial probe technique using an automated vector network analyzer (HP 8510). The spectra show two separate major dispersions (beta and gamma) and a much smaller dispersion between them. The two major dispersions are analyzed with a dispersion equation containing two Cole-Cole functions by means of a complex nonlinear least squares technique. The parameters of the equation at different temperatures have been determined. The low frequency behavior of the spectra suggests that the dielectric constant of the cell membrane increases when the temperature is above 35 degrees C. The real part of the dielectric constant at approximately 3.4 GHz remains almost constant when the temperature changes. The dispersion shifts with temperature in the manner of a thermally activated process, and the thermal activation enthalpies for the beta- and gamma-dispersions are 9.87 +/- 0.42 kcal/mol and 4.80 +/- 0.06 kcal/mol, respectively.